1997
DOI: 10.1046/j.1469-8137.1997.00822.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping physiological traits in barley

Abstract: SUMMARYAmplified fragment length polymorphisms (AFLPs) offer a reproducible, multiplex DNA assay by which to genotype mapping populations. We have evaluated physiological traits in barley seedlings grown in an hydroponic system and given a salt treatment. Multiple regression was used to show associations between AFLPs and quantitative traits. Effects at different loci were detected in stress treatments in comparison to the control implying that either novel gene action was induced by salt stress or that normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 20 publications
1
15
0
1
Order By: Relevance
“…Nevertheless, the high root growth found in lines containing the 4H chromosome of barley, irrespective of the parents, indicated the presence of quantitative trait loci (QTL) for root elongation on chromosomes 4H. A similar association was found previously by Raman et al [19], Jefferies et al [28] and Ellis et al [29] under different stress conditions. When evaluating the Al tolerance level of these introgression lines and parental genotypes, similar results were found by monitoring root growth and by the haematoxylin test.…”
Section: Discussionsupporting
confidence: 66%
“…Nevertheless, the high root growth found in lines containing the 4H chromosome of barley, irrespective of the parents, indicated the presence of quantitative trait loci (QTL) for root elongation on chromosomes 4H. A similar association was found previously by Raman et al [19], Jefferies et al [28] and Ellis et al [29] under different stress conditions. When evaluating the Al tolerance level of these introgression lines and parental genotypes, similar results were found by monitoring root growth and by the haematoxylin test.…”
Section: Discussionsupporting
confidence: 66%
“…At the vegetative stage, QTLs for salt tolerance in barley were found on chromosomes on group 1, 4, 6 and 7 (Ellis et al 1997). A later study by Ellis et al (2002) with different barley parents reported QTLs for salt tolerance at the vegetative stage on chromosomes 2, 5 and 7.…”
Section: Discussionmentioning
confidence: 96%
“…The first quantitative trait loci (QTL) identified for D 13 C was reported in tomato (Lycopersicon esculentum and L. pennellii) by Martin and Nienhuis (1989) and subsequently QTL for D 13 C have been reported in Arabidopsis thaliana Juenger et al 2005), barley (grain) (Teulat et al 2002), cotton (Gossypium hirsutum and G. barbadense) (Saranga et al 2001), rice (Oryza sativa L.) (Laza et al 2006;Takai et al 2006;This et al 2010;Xu et al 2009), soybean (Glycine max L.) (Specht et al 2001) and bread wheat (Triticum aestivum L.) (Rebetzke et al 2008). Ellis et al (1997) discovered several AFLP (amplified fragment length polymorphisms) markers associated with wholeshoot D 13 C of barley measured on 57 doubled haploids (DHs) from a cross between H. vulgare L. cv Lina and H. vulgare ssp. spontaneum HS92 in a hydroponic system under controlled and salt-stress conditions.…”
Section: Introductionmentioning
confidence: 99%